2022
DOI: 10.1002/ar.24996
|View full text |Cite
|
Sign up to set email alerts
|

Differential influence of YAP1 and TAZ on differentiation of intestinal epithelial cell: A review

Abstract: Intestinal cell stemness, proliferation and differentiation are complex processes all occurring in distinct compartments of the crypt that need to be closely regulated to ensure proper epithelial renewal. The involvement of the Hippo pathway in intestinal epithelial proliferation and regeneration after injury via the regulation of its effectors YAP1 and TAZ has been well-documented over the last decade. The implication of YAP1 and TAZ on intestinal epithelial cell differentiation is less clear. Using intestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…Intriguingly, our study revealed that the inhibitor VT105 affects YAP and TAZ differently. This differential response to the same small molecule adds to the growing body of evidence that, despite their many similarities and previous treatment as redundant, YAP and TAZ exhibit differences in expression, activation, and function. Moreover, crystal structures of YAP-TEAD and TAZ-TEAD complexes have revealed that TAZ-TEAD can engage in an additional heterotetramer binding mode not observed with YAP-TEAD . In this unique binding mode, the previously identified binding Interfaces 1 and 2 remain unchanged, but Interface 3 loses all of its hydrogen bonds except that of Trp43 .…”
Section: Discussionmentioning
confidence: 87%
“…Intriguingly, our study revealed that the inhibitor VT105 affects YAP and TAZ differently. This differential response to the same small molecule adds to the growing body of evidence that, despite their many similarities and previous treatment as redundant, YAP and TAZ exhibit differences in expression, activation, and function. Moreover, crystal structures of YAP-TEAD and TAZ-TEAD complexes have revealed that TAZ-TEAD can engage in an additional heterotetramer binding mode not observed with YAP-TEAD . In this unique binding mode, the previously identified binding Interfaces 1 and 2 remain unchanged, but Interface 3 loses all of its hydrogen bonds except that of Trp43 .…”
Section: Discussionmentioning
confidence: 87%
“…This differential response to the same small molecule adds to the growing body of evidence that, despite their many similarities and previous treatment as redundant, YAP and TAZ exhibit differences in expression, activation, and function. [49][50][51][52][53] Moreover, crystal structures of YAP-TEAD and TAZ-TEAD complexes have revealed that TAZ-TEAD can engage in an additional heterotetramer binding mode not observed with YAP-TEAD. 8 In this unique binding mode, the previously identified binding Interfaces 1 and 2 remain unchanged, but Interface 3 loses all of its hydrogen bonds except that of Trp43.…”
Section: Discussionmentioning
confidence: 99%
“…YAP1 and TAZ have a recognized involvement in intestinal epithelial cell regeneration and fate, and play important functions in epithelial repair and healing after injury (Deng et al, 2022) while DAPKs have a prominent function in programmed cell death (Bialik & Kimchi, 2006). The review by Fallah and Beaulieu (2022) offers an update of recent findings highlighting important differences between the activities of YAP1 and TAZ, which had been so far considered to exert largely overlapping and complementary functions. In turn, Chen and MacDonald (2022) present a comprehensive review on the DAPKs family, giving a detailed account of the known functions of all family members.…”
Section: Introductionmentioning
confidence: 99%